Female coming of age: A content analysis approach of digital humanities in Joyce Carol Oates’s Mudwoman (2012) - Mi, Chen; Omar, Noritah; Zainal, Zainor Izat; Awang, Mohammad Ewan (Academy Publication, 2023)
This study explores the theoretical basis and ways to realize the integration of contemporary digital technology and literary research, and looks forward to the analysis of the application of digital literary research by using Joyce Carol Oates’s novel Mudwoman (2012). The novel expresses great concern for the social crisis and the spiritual dilemma of human beings in contemporary America through the observation of the daily life of individuals in America. The previous research results of Mudwoman tend to make subjective judgments by traditional literary research methods, lacking relevant data support and innovative research perspectives and methods. In this study, we analyze the text of Mudwoman with a combination of content analysis based on digital humanities perspective. The results of this study reveal that M.R.’s coming of age is a path of identity search. In general, M.R. experiences childhood abandonment and kinship alienation, and the construction of her self-identity is fractured. It leads to the distress of interpersonal interactions in adulthood, aggravating her identity crisis. But with the help of kinship, she faces her past and predicament, returns to her spiritual home, reconciles with her past, and thus achieves the reconstruction of her identity.